Infectious disease and diabetes - Sanjay Kalra; Suneet Kumar Verma; Jatin Ahuja (Journal of the Pakistan Medical Association, 2023)
In this communication, we provide a bird’s eye view of the various ways in which infectious diseases intersect with diabetes. We list the ways in which infectious diseases can influence glucose homoeostasis and diabetes management, and explores how diabetes care is associated with infections and infection management. This is especially important for health care providers in regions with a high burden of infectious disease. Keywords: Bacteria, communicable disease, fungus, protozoa, virus.